Cutaneous T-cell lymphoma of the mycosis fungoides type: report of case series - Souza, Yan de Castro; Nicacio, Jandir Mendonça; Dias Neto, Fernando; Garcia de Oliveira, Heverton; Ribeiro, Dannyel Macedo; Fernandes, Tania Rita Moreno de Oliveira (Brazilian Journal of Case Reports, 2024)
Cutaneous T-cell lymphomas represent a heterogeneous group of lymphoproliferative diseases characterized by skin infiltration by mature malignant T cells. More than 40% of cutaneous T-cell lymphomas are represented by mycosis fungoides. As they present non-specific cutaneous manifestations, they are often underdiagnosed. This article reports four cases of mycosis fungoides with different subtypes treated by a multidisciplinary team, highlighting aspects related to clinical heterogeneity and diagnostic, therapeutic and differential diagnostic challenges, followed by a brief review of the literature. The cases described demonstrate the heterogeneity of cutaneous and systemic clinical signs, with presentations that present a significant diagnostic challenge due to other diseases with similar manifestations, especially for non-specialist physicians in basic healthcare units. Mycosis fungoides continues to be a problematic diagnosis, as the cases described had varied presentations and numerous inconclusive biopsies. Low clinical suspicion and technical limitations in the analysis of biopsies of skin lesions were the main factors implicated. It is hoped that this series of cases will bring a better understanding of the diagnostic aspects of this disease.